An L2 SUMO interacting motif is important for PML localization and infection of human papillomavirus type 16. (12th March 2014) - Bund, Timo; Spoden, Gilles A.; Koynov, Kaloian; Hellmann, Nadja; Boukhallouk, Fatima; Arnold, Philipp; Hinderberger, Dariush; Florin, Luise
Summary Human papillomaviruses (HPV) induce warts and cancers on skin and mucosa. The HPV16 capsid is composed of the proteins L1 and L2. After cell entry and virus disassembly, the L2 protein accompanies the viral DNA to promyelocytic leukaemia nuclear bodies (PML‐NBs) within the host nuclei enabling viral transcription and replication. Multiple components of PML‐NBs are regulated by small ubiquitin‐like modifiers (SUMOs) either based on covalent SUMO modification (SUMOylation), or based on non‐covalent SUMO interaction via SUMO interacting motifs (SIMs). We show here that the HPV16 L2 comprises at least one SIM, which is crucial for the L2 interaction with SUMO2 in immunoprecipitation and colocalization with SUMO2 in PML‐NBs. Biophysical analysis confirmed a direct L2 interaction with SUMO substantiated by identification of potential L2–SUMO interaction structures in molecular dynamics simulations. Mutation of the SIM resulted in absence of the L2–DNA complex at PML‐NB and in a loss of infectivity of mutant HPV16 pseudoviruses. In contrast, we found that L2 SUMOylation has no effect on L2 localization in PML‐NBs and SUMO interaction. Our data suggest that the L2 SIM is important for L2 interaction with SUMO and/or SUMOylated proteins, which is indispensable for the delivery of viral DNA to PML‐NBs and efficient HPV infection.